1993
DOI: 10.1093/bja/71.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Re-Expansion of Atelectasis During General Anaesthesia: A Computed Tomography Study

Abstract: Formation of atelectasis is one mechanism of impaired gas exchange during general anaesthesia. We have studied manoeuvres to re-expand such atelectasis in 16 consecutive, anaesthetized adults with healthy lungs. In group 1 (10 patients), the lungs were inflated stepwise to an airway pressure (Paw) of 10, 20, 30 and 40 cm H2O. In group 2 (six patients), three repeated inflations up to Paw = 30 cm H2O were followed by one inflation to 40 cm H2O. Atelectasis was assessed by analysis of computed x-ray tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
0
28

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(232 citation statements)
references
References 16 publications
7
193
0
28
Order By: Relevance
“…Obviously, airway pressure is another relevant factor. 13 Applying the same airway pressure for a prolonged time does not necessarily result in re-opening of more lung units if the critical opening pressure of the respective lung units is not exceeded. Thus extending the time of inflation further may simply increase adverse cardiovascular effects without additional beneficial effects in terms of improved oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, airway pressure is another relevant factor. 13 Applying the same airway pressure for a prolonged time does not necessarily result in re-opening of more lung units if the critical opening pressure of the respective lung units is not exceeded. Thus extending the time of inflation further may simply increase adverse cardiovascular effects without additional beneficial effects in terms of improved oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…13 14 Using this manoeuvre, the amount of pulmonary shunt may be reduced and, despite a concomitant increase in perfusion to poorly ventilated lung units (low VA/Q), this may result in a small but significant reduction in PA O2 -Pa O 2 for at least 40 min. 15 In several investigations, [13][14][15][16] the VC manoeuvre was performed by applying the inflation pressure of 40 cm H 2 O to the lungs for 15 s. Such a manoeuvre might result in adverse cardiovascular effects. 17 Reducing the time of maximal inflation to a few seconds may improve the margin of safety of such a manoeuvre.…”
mentioning
confidence: 99%
“…8 Atelectasis responds to higher ventilator volumes, probably because of the combination of enhanced release of surfactant which prevents further alveolar collapse, 15 ± 17 and the recruitment of additional lung elements. 18 Moreover, tetraplegics spend much of their time supine, a position that reportedly requires larger ventilator volumes to insure ventilation and perfusion of basilar lung regions and further prevent atelectasis and respiratory complications. 6 The ®ndings of this research are clouded somewhat by the fact that there were not wide di erences in the volumes used with the LTV and HTV groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bendixen et al [4] and later Rothen et al [7] showed that this pressure is approximately 40 cm H 2 O. Lachmann et al [8] recommended opening collapsed lungs by applying sufficient levels of peak inspiratory pressure and maintaining alveoli open by using sufficient levels of positive end-expiratory pressure (PEEP). This recruitment maneuver has been shown to improve arterial oxygenation and lung compliance [9].…”
Section: Anesthetic Concernsmentioning
confidence: 99%